On Theoretical Accuracy of Meteorological Targets Measurement by Radar - Fišer, Ondřej; Kovalchuk, Maria (Vysoké učení technické v Brně, 2022)
We draw your attention to the fact that meteorological radar does not actually measure a commonly used quantity “radar reflectivity factor,” (which is not dependent on frequency) but a different quantity called “radar reflectivity.” We present the usual recalculation which is based on frequency dependency used by Rayleigh approximation of radar cross-sections (back scattering cross section of rain, cloud, fog drop). But this approximation is valid in Rayleigh region only. We concluded that for admitting error lower than 2 dB in the radar reflectivity factor determination we can use the “effective radar reflectivity factor” for frequencies up to 19 GHz only. Otherwise the error will increase. As we use (and present in this article) the Mie algorithm we can replace the Rayleigh frequency dependence estimation by more accurate radar reflectivity factor determination using the Mie scattering. The correction is presented in the form of “Correction function C” dependent on frequency and rain rate in the graphical form and polynomial approximation. Beside this we present the simplification of back scattering cross sections for Rayleigh and Optical regions and the border values of size parameter for these regions. We added the meteorological radar equation derivation. This should support the radar measurement understanding.
K teoretické přesnosti radarových měření meteorologických cílů
Keywords: electromagnetic reflection; meteorological radar; radar cross-sections; radar measurements; elektromagnetický odraz; meteorologický radar; zpětné odrazové plochy; radarová měření